an=n,bn=2^n若Cn=anbn,求数列(cn)的前n项和sn
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 17:11:33
an=n,bn=2^n若Cn=anbn,求数列(cn)的前n项和sn
an=n,bn=2^n若Cn=anbn,求数列(cn)的前n项和sn
an=n,bn=2^n若Cn=anbn,求数列(cn)的前n项和sn
s(n)=1*2+2*2^2+3*2^3+...+(n-1)*2^(n-1)+n*2^n
2s(n)=1*2^2+2*2^3+3*2^4+...+(n-1)*2^n+n*2^(n+1)
-s(n)=s(n)-2s(n)=2+2^2+...+2^n - n*2^(n+1)
=2[2^n-1] - n*2^(n+1)
s(n)=n*2^(n+1)-2^(n+1)+2=2+(n-1)*2^(n+1)
错位相减法。
Cn=n*2^n
Sn=C1+C2+C3+...+Cn
=1*2^1+2*2^2+3*2^3+...+n*2^n
2Sn=2*1*2^1=2*2*2^2+2*3*2^3+...+2*n*2^n
=1*2^2+2*2^3+3*2^4+...+n*2^(n+1)
2sn-sn=1*2^2+2*2^3+3*2^4+...+n*2^(n+1)-(1*2^1+2*2^2+3*2^3+...+n*2^n)
sn=-1*2^1-1*2^2-1*2^3-...-1*2^n+n*2^(n+1)
=2(2^n-1)+n*2^(n+1)
=(n+1)*2^(n+1)-2
Cn=n*2^n 数列sn=2+2*2²+3*2³+…+(n-1)*2^(n-1)+n*2^n
2sn=2²+2*2³+3*2^4+…+(n-1)*2^n+n*2^(n+1),sn-2sn=2+2²+2³+…+2^n-n*2^(n+1),
sn=n*2^(n+1)-2*(2^n-1)=(n-1)*2^(n+1)+2